IMPLEMENTASI MULTI ATTRIBUTE DECISION MAKING MENGGUNAKAN METODE WEIGHTED PRODUCT DALAM PEMILIHAN SUPERVISOR - Hidayanti Murtina; Nunung Hidayatun; Susafa’ati Susafa’ati (Universitas Teknokrat Indonesia, 2022)
The selection of supervisors is important because it will show good employee performance. With supervisors, selection employees can look to give their best work because they know that their performance is on the way. Seeing the importance of a supervisor, it would be even better if stakeholders used a method of assessment in decisions so that previous assessments could produce even better decisions. Sometimes making a decision on an appropriate decision is based on subjective, which is caused by the attachment between stakeholders with one of the choices that ends in a reduced sense of appreciation or the chosen outcome. By using the help of a decision support method, the results or outcomes of the resulting decisions will be of more objective value. The author will conduct research with the help of the Multi-Attribute Decision Making (MADM) method and the method that will be used in this research is the weighted product (WP) method. The criteria that the author uses in this study include intellectual ability, personality, work attitude, thinking ability, self-management, task management and human resource management in accordance with the supervisor selection criteria at PT. Nippon Indosari Corpindo. The final result of this research is the election of A9 with the name Suhelmi with a value of 0.1160 as the surest candidate as a supervisor followed by alternative A3 Cipto Agung with a value of 0.1142 in the 2nd position and alternative A2 Asa Sofia with a score of 0.1090 in the position the 3rd